Implementasi penanaman sikap tasamuh siswa dalam program Profil Pelajar Rahmatan Lil ‘Alamin MAN 2 Lamongan - Candra, Zaqias (Maliki Interdisciplinary Journal, 2024)
The background to this research is based on the implementation of the Merdeka Curriculum in the 2022/2023 academic year which introduced the Pancasila Student Profile and the Rahmatan lil 'Alamin Student Profile (P5PPRA). The main goal of national education is to form students with good character, one of which is an attitude of tasamuh (tolerance). This research aims to analyze the implementation of the tasamuh attitude in the PPRA program at MAN 2 Lamongan and identify the problems faced in improving students' tasamuh character. The research method used is descriptive qualitative with a classroom action research approach. Data was collected through classroom observations, interviews with teachers and students, and documentation. And the subjects of this research are teachers and students of MAN 2 Lamongan for the 2023/2024 academic year. Implementation of the tasamuh attitude is carried out through preparation, implementation and follow-up phases. In the preparation phase, Tasamuh character values ​​are integrated with the Pancasila Student Profile. The implementation phase involves activities such as still life drawing, discussions about individual diversity, and visits to Pancasila Village. The follow-up phase includes evaluating and strengthening tasamuh attitudes through observation, reflection and action surveys. The research results show that the P5PPRA program can improve students' understanding and attitude of tasamuh, despite facing several challenges. These challenges include a lack of clarity on PPRA elements and indicators, a lack of clarity on assessment aspects and indicators, the homogeneity of the madrasa environment, as well as difficulties in cultivating and changing student character. The conclusion of this research is that the P5PPRA program can be successful in instilling tasamuh attitudes if it is supported by the active role of families, communities and schools. Effective implementation and adaptation based on local wisdom is very important to overcome existing challenges.